STUDENT ATTENDANCE SYSTEM USING WIFI DIRECT AND TEMPORARY WI-FI HOTSPOT - Doni Setio Pambudi; Taufiqotul Bariyah (Jurnal Ilmu Komputer dan Informasi, 2020)
Manual attendance recording throws away a lot of teaching and administration time from the university. Research on automatic attendance recording that has been done can be divided into biometrics and non-biometrics uses. Almost all methods require additional device that it is costly and inflexible for class changes. The proposed method solves the problems by utilizing the standard features of smartphones that are owned by all student, this method uses Wi-Fi direct for class broadcasting process and temporary Wi-Fi hotspot for verification process. The experimental results show that the proposed method produces the time needed for the initialization process is 14980 ms and the verification process is 3640 ms.